Peningkatan Hasil Belajar Tematik Terpadu Menggunakan Model Problem-Based Learning di Kelas V Sekolah Dasar - A.R., Faresti Dwilanda; Muhammadi, Muhammadi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2023)
This classroom action research was carried out because student learning outcomes were still relatively low, this was due to the preparation of lesson plans and the learning process that had not been carried out optimally. The aim is to describe the increase in students learning outcomes in integrated thematic learning using the Problem-Based Learning Model in Class V SDN 10 Bandar Buat Padang City. This study used a quantitative and qualitative approach with the research subject being the teacher and fifth-grade students at SDN 10 Bandar create and carried out in 2 cycles. The designs in this study are (1) planning, (2) implementation, (3) observation, and (4) reflection. The results of the research show that the aspects observed have increased, namely: a) lesson plans in Cycle I 94.4% (SB) Cycle II 97.7% (SB), b) teacher activities in Cycle I 83.9% (B), Cycle II 96.4% (SB), c) student activities in cycle I 82.2% (B), Cycle II 96.4% (SB), and d) student learning outcomes in cycle I 76.1 (B), rose in cycle II to 87.5 (B). Thus, it was concluded that the Problem-Based Learning (PBL) model could improve student learning outcomes in integrated thematic learning in class V SDN 10 Bandar Buat Padang City.